PERTANGGUNGJAWABAN EMITEN TERHADAP KERUGIAN INVESTOR AKIBAT KELALAIAN EMITEN YANG MENGAKIBATKAN PENGHENTIAN SEMENTARA PERDAGANGAN EFEK (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
One of the problem that often occurs at Stock Market is a lack of protectiontowards Investors due to The Isser’s negligence that causing loss for Investors, especially when due that negligence causing Stock Exhange Suspension at Stock Market.This research is a normative research. This research is done by studying all the laws and regulations that related to tyhe main issue of the problem. On this research, approaching method that used is a descriptive method.The rsult of the study shows how is the rights and obligations between The Issuer and The Investors, also how is The Issuer’s responbility towards Investors loss due to The Issuer negligence that causing Stock Exhange Suspension at Stock Market. First, according to article 54 and 55 of KUHD, is just briefly explain Investor’s voting rights due to their Stock Ownership and The Issuer’s obligations to make the report abaout profit and loss. Then according to article 51 of UU PT, Investor have rights to file a lawsuit, ask The Issuer to buy Investors stock and ask General Meeting of Shareholders (RUPS) to be held. The Issuers responbility due to Investors loss written at UU PT, UU PM, and UU OJK which don’t explain too much about The Issuer’s accountability. From this research, it can be concluded that the regulations about the rights and obligations between The Issuer and Investors included at some laws, but it’s not describing enough, especially abot The Issuer’s accountability towards Investor’s loss due to Stock Exhange Suspension, which explain that there is an urgent needs for a main Law and Regulations abaout Stock Market in Indonesia.Keywords : Issuer – Investors - Responbility – Stock Exhange Suspension